Comparison Between Vetiver and Brachiaria Grass in Erosion Control in Tropical Climate - Mario Guilherme Garcia Nacinovic; Cláudio Fernando Mahler; Maria Clara de Oliveira Marques; José Ronaldo de Macedo; Adoildo da Silva Melo; Guilherme Ottoni Souza; Renata Coura Borges (Sustainable Chemical Engineering, 2024)
The use of conservation practices, such as level planting and the use of cover crops, can reduce the magnitude of erosion processes, reducing losses of soil, water, nutrients, and organic carbon. The aim of this study was to compare erosion control using vetiver, bare soil, and brachiaria grass. The experiment was carried out over a period of ten months, representing the rainy season in the humid tropical climate of Rio de Janeiro. Erosion was monitored on three Gerlach-type runoff erosion plots with different types of soil cover. Erosion was quantified by analyzing the sediment in runoff samples using the following methods: 1) the evaporation method described in APHA-Standard Methods 2540 B (2005) when the sediment concentration was greater than 200 mg·L-1, and 2) the filtration method described in APHA-Standard Methods 2540 D (2005) when the sediment concentration was less than 200 mg·L-1. During an extreme heavy rainfall event (precipitation of 38.8 mm and rainfall intensity of 13.6 mm·h-1), the vetiver system showed erosion of 1.04 kg·ha-1, while the brachiaria grass had erosion values of 41.66 kg·ha-1. Thus, it is clear that vetiver was more efficient at controlling erosion due to its deep fasciculated roots, which enhance infiltration, and its vegetative character, which forms a physical barrier and slows down runoff, reducing erosive energy and retaining sediment. On the other hand, the bare soil showed erosion of 2,531.61 kg·ha-1, highlighting the efficiency of using grasses to control erosion.